Review of Electrochemical Technologies for Environmental Applications - Drogui, Patrick; Blais, Jean-Francois; Mercier, Guy (Recent Patents on Engineering, 2007)
This review deals with electrochemical methods for water, wastewater, wastes and soils treatment. The electrochemical technique combines both physical chemistry and electronic science and has widely proved to be a clean, flexible and powerful tool for the development of new methods for waste and water treatment. Likewise, electrochemical treatment is generally characterized by simple equipment, ease of operation, short retention time and negligible equipments for adding chemicals. Besides, electrolytic cells can be easily automated and coupled with other processes including, biological, chemical and physical processes to enhance the efficiency of the treatment. A particular focus is given to electrocoagulation (EC), electrodeposition (ED), electroflotation (EF), electrokinetic (EK) and electrooxidation (EO) processes. These technologies are effective in improving the treatment quality of industrial wastes, wastewaters and drinking water on integration into a treatment plant or replacement of conventional processes that are found to be less effective to eliminate specific organic and inorganic pollutants. EC can be used for clarifying water or to eliminate organic, inorganic and microbial pollutants from wastewater. The technology delivers in situ coagulant by anodic dissolution of sacrificial electrodes (aluminium or iron) and is finding wider applications with the possible improvements in the reduction of energy consumption and metallic sludge production. ED is a well-established process for toxic metal removal whose effectiveness can be greatly improved by selecting suitable electrode material (type and geometry of the electrode). EF technology is effective in removing suspended solids, colloidal particles and oil & grease suspension. EK technology is a promising method to remove toxic metals from the matter with low hydraulic permeability or to enhance dewaterability of wastes including soils and sludge. The development of new, more stable and active catalytic electrodes has led to a renewed interest in EO for degrading refractory organic pollutants. This paper covers both established and recent developments in the field of electrochemical technologies for waste, water and wastewater treatment based on more than 158 patents and publications cited or analyzed.
Keywords: wastes